PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA SEBAGAI SARANA PEMBERDAYAAN KETERAMPILAN PEMBUATAN PUPUK KOMPOS - Mumtaz, Ahmad Fairuz; Widiyanto, Delfiyan; Swasono, Adhi; Wulandari, Dewi; Ramadhan, Ichsan Wahyu; Aryantina, Reza; Prabowo, Rezky Asyidiq; Putri, Rosewita Akhmellia; Ningsih, Salsabillah Aulia; A'yunin, Qurrota; Anggraeni, Yuniar Fitri (Kohesi: Jurnal Sains dan Teknologi, 2025)
This study focuses on sustainable waste management efforts in Kaliabu Village, Magelang Regency, through socialization and practical training on compost production involving PKK members. The initiative aims to address household waste issues by promoting effective waste management solutions, such as composting organic waste. The training covered the selection of appropriate materials, preparation techniques, and maintenance methods to ensure high-quality compost production. The results showed that the compost produced after three weeks exhibited optimal characteristics, such as a crumbly texture, dark brown color, and a fresh earthy aroma. This initiative is expected to encourage active community participation in sustainable waste management while providing economic and environmental benefits.